The Nest [compact disc, unabridged] - Sweeney, Cynthia D'Aprix (Harper Audio, 2016)
It is a warm, funny, and acutely perceptive debut novel about four adult siblings and the fate of the shared inheritance that has shaped their choices and their lives. Years of simmering tensions finally reach a breaking point after an ensuing accident endangers the Plumbs' joint trust fund, which they are months away from finally receiving. The Plumb siblings have been counting on the money to solve a number of self-inflicted problems. Brought together as never before, Leo, Melody, Jack, and Beatrice must grapple with old resentments, present-day truths, and the significant emotional and financial toll of the accident, as well as finally acknowledge the choices they have made in their own lives. Sweeney brings a remarkable cast of characters to life to illuminate what money does to relationships, what happens to our ambitions over the course of time, and the fraught yet unbreakable ties we share with those we love.